Role of Marketing Concepts in Increasing Product Competitiveness - Musayeva Shoira Azimovna (International Journal on Economics, Finance and Sustainable Development, 2021)
In this article, the content of the concept of consumer marketing today is also characterized by the choice of a specific target segment and its high quality, comprehensive service and the role of customer relationships.